1995
DOI: 10.1002/mc.2940130306
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations in matched primary and metastatic human tumors

Abstract: Mutations in the p53 tumor suppressor gene have been found to be the most frequent genetic alterations in human malignancies. To further examine the idea that neoplastic progression is associated with mutations in the p53 gene, we analyzed matched primary and metastatic tumor samples. The samples included 15 pairs of breast cancer and metastases to lymph nodes, four pairs of gastrointestinal adenocarcinomas and metastases to liver, one colon adenocarcinoma and metastasis to a lymph node, and one lung carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…This finding is in contrast to colonic adenocarcinomas that typically demonstrate higher rates of mutation for TP53 and reactivity to p53. 5,16,17,19,20 I I I ANI I I ANI I I ANI I 0/8 REAH2 ANI ANI I ANI LOH I I I I LOH I 2/8 REAH3 LOH ANI ANI I LOH LOH LOH I I LOH LOH 6/9 REAH4 ANI ANI LOH I ANI I ANI I I LOH LOH 3/7 REAH5 NI A...…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in contrast to colonic adenocarcinomas that typically demonstrate higher rates of mutation for TP53 and reactivity to p53. 5,16,17,19,20 I I I ANI I I ANI I I ANI I 0/8 REAH2 ANI ANI I ANI LOH I I I I LOH I 2/8 REAH3 LOH ANI ANI I LOH LOH LOH I I LOH LOH 6/9 REAH4 ANI ANI LOH I ANI I ANI I I LOH LOH 3/7 REAH5 NI A...…”
Section: Discussionmentioning
confidence: 98%
“…Abnormalities of p53 are frequently found in human breast cancer and have important clinical implications [3,[11][12][13]16,17,22]. A number of studies have shown that tumors lacking wild-type p53 are likely to have a relatively poor prognosis [3,23].…”
Section: Resultsmentioning
confidence: 99%
“…Work in a number of systems has suggested that the T AG protein disrupts the regulation of cellular growth by interacting with key nuclear proteins such as p53 and pRb, which normally function to regulate cell proliferation [8][9][10]. Mutations in the tumor suppressor gene p53 are known to occur in over 50% of human tumors, including metastatic breast cancers [11][12][13]. p53 mutations can occur at various stages in carcinogenesis and have various effects on its progression [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…9 The p53 gene exhibits several mutations both in coding and noncoding regions, namely single nucleotide polymorphisms (SNPs) in exon 4 at codon 72 10,11 and intron 6. 12 Ara et al 13 reported that the above two mutant varieties are functionally distinct from their wild type gene product because of inequalities in both their biological and biochemical properties.…”
Section: Introductionmentioning
confidence: 99%